Retinoic Acid is Required for Normal Morphogenetic Movements During Gastrulation - Gur, Michal; Edri, Tamir; Moody, Sally A.; Fainsod, Abraham (Frontiers in Cell and Developmental Biology, 2022)
Retinoic acid (RA) is a central regulatory signal that controls numerous developmental processes in vertebrate embryos. Although activation of Hox expression is considered one of the earliest functions of RA signaling in the embryo, there is evidence that embryos are poised to initiate RA signaling just before gastrulation begins, and manipulations of the RA pathway are reported to show gastrulation defects. However, which aspects of gastrulation are affected have not been explored in detail. We previously showed that partial inhibition of RA biosynthesis causes a delay in the rostral migration of some of the earliest involuting cells, the leading edge mesendoderm (LEM) and the prechordal mesoderm (PCM). Here we identify several detrimental gastrulation defects resulting from inhibiting RA biosynthesis by three different treatments. RA reduction causes a delay in the progression through gastrulation as well as the rostral migration of the goosecoid-positive PCM cells. RA inhibition also hampered the elongation of explanted dorsal marginal zones, the compaction of the blastocoel, and the length of Brachet’s cleft, all of which indicate an effect on LEM/PCM migration. The cellular mechanisms underlying this deficit were shown to include a reduced deposition of fibronectin along Brachet’s cleft, the substrate for their migration, as well as impaired separation of the blastocoel roof and involuting mesoderm, which is important for the formation of Brachet’s cleft and successful LEM/PCM migration. We further show reduced non-canonical Wnt signaling activity and altered expression of genes in the Ephrin and PDGF signaling pathways, both of which are required for the rostral migration of the LEM/PCM, following RA reduction. Together, these experiments demonstrate that RA signaling performs a very early function critical for the progression of gastrulation morphogenetic movements.